(untitled) (KONFERENSIYA, 2025)
This article discusses what translator etiquette really means and why it matters in everyday translation work. Instead of focusing only on technical skills, it looks at the behaviors, attitudes, and ethical choices that help translators work responsibly and respectfully. It also emphasizes the importance of continuous learning and professionalism. By bringing these points together, the article shows how good etiquette not only improves translation quality but also builds trust and strengthens meaningful communication across languages and cultures